Case Report: A potential novel treatment for drug-induced acute interstitial nephritis: Benralizumab - Saadia, Alexander; Wald, Ron; Potruch, Assaf; Pizov, Galina; Meir, Karen; Gorin, Kobi; Sarig, Inon; Dori, Eyal Ben; Rubin, Limor; Ribak, Yaarit; Shamriz, Odded; Tal, Yuval; et al. (Frontiers in Immunology, 2025)
A 55-year-old man presented to the emergency department (ED) with diffuse abdominal pain, vomiting, and anuria following a night of heavy alcohol intake. The patient’s medical history included hypertension. Two weeks prior to presentation, he was prescribed etoricoxib for back pain. On presentation, he was found to have severe acute kidney injury, and dialysis was initiated. Renal biopsy showed acute interstitial nephritis with numerous eosinophilic infiltrates. Despite stopping etoricoxib and initiating high-dose steroids, kidney function did not improve. The administration of benralizumab—an anti-CD125 antibody—resulted in rapid and complete recovery of kidney function. This case report highlights the potential role of benralizumab in the treatment of drug-induced interstitial nephritis with eosinophiluria.